Influence of bank specific factors, market concentration and macroecomic indicators towards Islamic and conventional banks stability in Indonesia - Nunung Aini Rahmah (Tanjong Malim, 2023)
Influence of bank specific factors, market concentration and macroecomic indicators towards Islamic and conventional banks stability in Indonesia by Nunung Aini Rahmah